2023
DOI: 10.1158/1541-7786.mcr-22-0623
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Tumor Microenvironment Analysis of Primary and Recurrent Ovarian Granulosa Cell Tumors

Abstract: Adult-type granulosa cell tumors (aGCT) are rare ovarian sex cord tumors with few effective treatments for recurrent disease. The objective of this study was to characterize the tumor microenvironment (TME) of primary and recurrent aGCTs and to identify correlates of disease recurrence. Total RNA sequencing (RNA-seq) was performed on 24 pathologically confirmed, cryopreserved aGCT samples, including 8 primary and 16 recurrent tumors. After read alignment and quality-control filtering, DESeq2 was used to identi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 67 publications
0
1
0
Order By: Relevance
“…Recently, this technique has been used to explore differences within ovarian, prostate, and brain tumors. 27–29 As scRNA-seq research continues to evolve, clinicians can better identify specific cancer subtypes and adjust treatment appropriately.…”
Section: The Tumor Microenvironmentmentioning
confidence: 99%
“…Recently, this technique has been used to explore differences within ovarian, prostate, and brain tumors. 27–29 As scRNA-seq research continues to evolve, clinicians can better identify specific cancer subtypes and adjust treatment appropriately.…”
Section: The Tumor Microenvironmentmentioning
confidence: 99%
“…Although trunctating KMT2D mutations, TERT promoter mutations and pathogenic TP53 variants have been reported in aGCT-cohorts, a pattern that describes prognostic markers is yet to be identified [17][18][19][20][27][28][29]. Interestingly, a recent study reported an increased expression of genes with hormone signalling functions in aGCT [30].…”
Section: Introductionmentioning
confidence: 99%
“…Although trunctating KMT2D mutations, TERT promoter mutations and pathogenic TP53 variants have been reported in aGCT-cohorts, a pattern that describes prognostic markers is yet to be identified [17][18][19][20][27][28][29]. Interestingly, a recent study reported an increased expression of genes with hormone signalling functions in aGCT [30].…”
Section: Introductionmentioning
confidence: 99%